PERENCANAAN DAN PERANCANGAN GEDUNG PERPUSTAKAAN DAN KEARSIPAN PROVINSI SUMATERA BARAT - 381-388 , Befaldo Angga (CIVED, 2014)
ABSTRACT   September 30, 2009 that happened in West Sumatera has destroyed the building of Library and Archieve of West Sumatera Province. Because the role of the Library and Archives Agency is so important and irreplaceable, the re-planning and re-design of the building need to be implemented. The purposes of planning and design of this building are (1) to asses space needs, (2) to determine the space layout, and (3) to design the building form and architectural concept. The applied design method consists of programming, planning, concept, and design. Analysis was performed in the form of macro analysis and micro analysis. The result of planning and design the building that has 3985,56 m2 47 rooms. In the first floor, there are the lobby room, public facilities and service room. In the second floor and third floor there are staff room, reading room, discussion room and digital library room. In the fourth floor there are hall and shelter. The architecture concepts are Minangkabau architecture and Indonesian traditional architecture. Keywords: Library, Planning, Design